Pathways to Sustainable Wheat Business Models: Exploring agroecological practices and investment opportunities in Doyogena, Ethiopia - Mosquera, Leslie Estefany; Blanco, Maria; Balcha, Yodit; Mockshell, Jonathan; Ritter, Thea (2025)
Ethiopia, the largest wheat producer in sub-Saharan Africa, relies heavily on wheat for both household income and food security. In the Dogoyena district in the southern part of the country, there is significant potential to advance agroecological practices within the wheat value chain. While most smallholders primarily depend on wheat for their livelihoods, many are beginning to diversify their crops as part of broader economic diversification efforts. This shift is occurring despite government initiatives promoting wheat intensification to meet growing national and international demand. Producers Doyogena is a critical project area for the Private Sector Incentives and Investments (PSii) under the TRANSITIONS program due to it has conditions that favor the cultivation of wheat, which is predominantly cultivated by smallholder producers in the district. This study focuses on four wheat clusters in the Dogoyena district: Tumma, Adoye, Selam, and Telle. This study is crucial as it will help identify the most effective incentives and investment opportunities within wheat clusters, considering the social and economic local contexts of the key stakeholders in the Dogoyena district. This report is part of the PSii project and provides an in-depth analysis of three cooperative business models in four wheat clusters, as well as of agroecological practices in Ethiopia. Utilizing focus group discussions and the Business Model Canvas tool, the study offers a comprehensive examination of wheat production strategies and their alignment with sustainable practices. The analysis of farmer cooperatives from four wheat farming clusters (Tumma, Adoye, Selam, and Telle) reveals distinct approaches to wheat production. Amecho Seed Multiplication cooperative (Adoyo cluster) and the Serara producer cooperative (Telle and Tumma cluster) focus on high-quality production and strong customer relationships, investing significantly in labor, inputs, and credit. Angacha producers Cooperative (Selam cluster) integrates resource sharing through partnerships while Serara emphasizes waste reduction and manages costs related to interest rates, storage, and transportation. The findings on agroecological practices show that producers have low engagement in market connectivity and integration, indicating a need for improved market linkages and cooperative development. Knowledge sharing and multi-stakeholder participation are also insufficient, emphasizing the need for better extension services and collaborative learning. Although some agroecological practices are adopted, there is significant potential for improvement in soil health, biodiversity, and fairness in income distribution. Encouraging practices like cover cropping, reduced tillage, and integrated pest management can enhance sustainability and resilience. This report analyzes the opportunities for improvement and appropriate investments and incentives to promote and support the transition towards more sustainable practices in the study area.